Learning Management Systems within a South African university: lecturers’ experiences and extent of use during and post COVID-19 - Mfingwana, Nwabisa (University of the Witwatersrand, Johannesburg, 2023)
The integration of technology in the education sector has resulted in pervasive use of Learning Management Systems (LMSs). Prior and during COVID-19, several higher education institutions within South Africa acquired and started using LMSs to enable and facilitate online teaching and learning. During COVID-19 when face-to-face learning was impossible due to lockdowns, LMSs became even more prominent, advancing from being learning support tools to becoming primary learning systems. While prior research claims that LMSs are underutilised, as the world transitions to the new normal, with hybrid learning being the latest learning method, LMSs appear to be just as significant. To explore the experiences and extent of use of LMS, this study employed the Will, Skill, Tool, and Pedagogy (WSTP) model. Using semi-structured interviews, data was collected from nine lecturers who teach technology and creative arts programs at a Johannesburg based university in South Africa. Findings indicate that even though lecturers view LMSs as a valuable tool, it is not a perfect fit for the needs and requirements of all university programmes. Furthermore, although use of LMSs grew exponentially and pervasively during COVID-19, post the pandemic lecturers’ use patterns are more varying. While some lecturers in the creative art programme are reducing or stopping their use of certain LMS features as they favour of in-person teaching and believe that the LMS may not be aligned to their teaching style. However, lecturers in technology are continuing their current use, and in some cases are even more curious and enthusiastic about the tool. Lastly, despite the reported benefits of LMSs such as content management and communication, challenges related to system constraints, functional limitations, infrastructure issues and limited technology and LMS skills were reported. Theoretically the study contributes to the body of knowledge about lecturers’ use of LMSs and illustrates how the WSTP model can be used in similar contexts. Practically the study highlights that a comprehensive needs and requirements analysis should be conducted by decision makers prior to implementing a one-fits-all approach, training and ongoing awareness of LMS features is critical to ensure that the system is used optimall
A research report submitted in partial fulfilment of the requirements for the degree of Master of Commerce to the Faculty of Commerce, Law and Management, School of Business sciences, University of the Witwatersrand, Johannesburg, 2023
Keywords: Learning Management System; LMSs; Technology; LMS; eLearning; Lecturers; COVID-19; Pandemic; WSTP; Higher education institutions; UCTD; SDG-4: Quality education